Types of Film Production Business Models and Their Interrelationship - Vitkauskaitė, Ieva (Information & Media, 2020)
Types of film production business models are not a widely studied area in the scientific literature, and more attention is paid to the production of individual films, specifics. In this article, ten types of business models of film production companies were analysed and systematized, and the relationships between them were established. The analysis of the models identified two main, major business models: the studio model and the Business model 2.0, which becomes part of all other business models. The studio model directly includes the vertical integration model. It also consists of a “Market-oriented” model, “Horizontal integration”, “Product-oriented” model. Business model 2.0 can consist of: “Long Tail”, “Free” model and “360 - degree” models.